Association of Low Back Pain with Sitting Patterns among Desk-Based Office Workers: Low Back Pain with Sitting Patterns among Desk-Based Office Workers - Rani, Laieba; Sukhera, Sadia; Siddique, Awais; Shafiq, Hira; Amjad, Fizzah; Imtiaz, Rameen (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2024)
Low back pain (LBP) is one of the most frequently observed musculoskeletal complaints of office workers who sit at the desk for most of their working hours, chiefly as a result of sitting and poor sitting postures. Since the sedentary working conditions are on the increase, it is essential to know the connection between sitting patterns and LBP. Objective: To determine the association of LBP with sitting patterns among desk-based office workers. Methods: The cross-sectional study was conducted at the University of Lahore for four months. A sample of 72 faculty members aged 25–55 years was selected using convenience sampling. Data were collected using a self-structured questionnaire covering demographic details, sitting patterns and pain severity, which was measured using the Visual Analogue Scale (VAS), a 10-point scale where 0 indicates 'no pain' and 10 indicates 'worst possible pain'. Statistical analysis was conducted by SPSS version 25.0, and the chi-square test assessed the association between variables. Results: The results showed 91.7% of participants reported experiencing LBP in the past year. Most participants (52.8%). Seated position for more than six hours per day, and 70.8% rated their posture as average. A significant number (58.3%) only occasionally supported their back properly, and 63.9% had monitors not aligned at eye level. The association between poor sitting habits and increased LBP was statistically significant (p<0.01). Conclusions: The present study shows a close relationship between LBP and sitting habits in office workers who sit at their workstations.